Frequency of Extracorporeal Membrane Oxygenation Support and Outcomes After Implementation of a Structured PICU Network in Neonates and Children: A Prospective Population-Based Study in the West of France. Issue 11 (November 2021) - Bourgoin, Pierre; Aubert, Lucie; Joram, Nicolas; Launay, Elise; Beuchee, Alain; Roue, Jean Michel; Baruteau, Alban; Fernandez, Modesto; Pavy, Carine; Baron, Olivier; Flamant, Cyril; Liet, Jean Michel; et al.
Abstract : OBJECTIVES: To describe the frequency and outcomes on the use of extracorporeal membrane oxygenation (ECMO) among critically ill neonates and children within a structured pediatric critical care network in the West of France. To assess the optimality of decision-making process for patients primarily admitted in non-ECMO centers. DESIGN: Observational prospective population-based study from January 2015 to December 2019. PATIENTS: Neonates over 34 weeks of gestational age, weighing more than 2, 000 g and children under 15 years and 3 months old admitted in one of the 10 units belonging to a Regional Pediatric Critical Care Network. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Eight-thousand one hundred eighty-nine children and 3, 947 newborns were admitted within one of the 10 units of the network over the study period. Sixty-five children (8.1% [95% CI, 6.2–10‰]) and 35 newborns (9.4% [95% CI, 6.4–12%]) required ECMO support. Of these patients, 31 were first admitted to a non-ECMO center, where 20 were cannulated in situ (outside the regional ECMO center) and 11 after transfer to the ECMO regional center. Cardiogenic shock, highest serum lactate level, and cardiac arrest prior to first phone call with the regional ECMO center were associated with higher rate of in situ cannulation. During the study period, most of the patients were cannulated for underlying cardiac issue (42/100), postoperative cardiac surgery instability (38/100), and pediatric (10/100) and neonatal (10/100) respiratory distress syndrome. Patients primarily admitted in non-ECMO centers or not had similar 28-day post-ICU survival rates compared with those admitted in the referral ECMO center (58% vs 51%; p = 0.332). Pre-ECMO cardiac arrest, ECMO, and lower pH at ECMO onset were associated with lower 28-day post-ICU survival. CONCLUSIONS: Our local results suggest that a structured referral network for neonatal and pediatric ECMO in the region of Western France facilitated escalation of care with noninferior (or similar) early mortality outcome. Our data support establishing referral networks in other equivalent regions. Abstract : Supplemental Digital Content is available in the text.